Economic Impact Analysis of Kecamatan Development Program Infrastructure Projects - Torrens, Anthony (World Bank, Washington, DC, 2015)
The Government of Indonesia and the World Bank commissioned this independent study to conduct a post-construction economic impact analysis on 113 Kecamatan Development Program (KDP) rural infrastructure projects to determine the overall economic benefits that have accrued to the villages that planned and built infrastructure facilities according to the KDP Community Driven Development approach. This study expands on the scale and scope of the initial economic analysis that was completed for 41 KDP projects in November 2001 under KDP 1. That study was limited to calculating Economic Internal Rates of Return only. In contrast, this study focuses on three main activities: (1) Assessing tangible benefits by calculating the Economic Internal Rates of Return for the four types of KDP rural infrastructure; (2) Analysing the overall macro-economic impact of new income generated by KDP infrastructure activities within the local village economies by using (i) a General Income Multiplier Analysis and (ii) Project-Specific Quality of Life Indicators to capture certain intangible benefits that have accrued since the project s completion; and (3) Undertake a Least-Cost Analysis by re-costing KDP infrastructure projects using local contractor rates to determine what the same project would cost if tendered out by local government to local contractors.